PENGETAHUAN PERAWAT TENTANG KESELAMATAN PASIEN DENGAN PELAKSANAAN PROSEDUR KESELAMATAN PASIEN RUMAH SAKIT (KPRS) DI RUMAH SAKIT PANTI WALUYA SAWAHAN MALANG - Bernadeta Dece Harus; Ani Sutriningsih (Care : Jurnal Ilmiah Ilmu Kesehatan, 2015)
Patient safety is a system created by the Hospital so that patient care safe. Which is supported by the knowledge and attitudes that are the result of the idea through to a particular object sensing and social interaction so that the formation of one's actions. The aim of research to determine the relationship of the nurse's knowledge about patient safety by implementing hospital patient safety procedures in Hospital Nursing Waluya Sawahan Malang. This study used a correlational design with cross sectional approach. The population in this study nurses were 60 respondents using simple random sampling technique. Digger questionnaire data. The data obtained were analyzed with a computerized program using Spearman Rank Test. The results of the research data showed the majority of 49 respondents (81.7%) have sufficient knowledge and fraction 3 respondents (5.0%) knowledgeable good. Whereas in the implementation of Hospital Patient Safety mostly 41 respondents (68.3%) Less Patient Safety implementation and fraction 3 respondents (5.0%) Patient Safety good execution. Analysis of the data by the Spearman Rank test was obtained (p value) (0,001)